2005
DOI: 10.1163/156853905774405308
|View full text |Cite
|
Sign up to set email alerts
|

The roles of male size and female eavesdropping in divorce in the monogamous convict cichlid (Archocentrus nigrofasciatus, Cichlidae)

Abstract: In this experiment we examined the roles of male size and female eavesdropping in divorce using the serially monogamous convict cichlid (Archocentrus nigrofasciatus) by testing predictions based upon the better option hypothesis of divorce. We tested the role of male size by exposing females to males that were 20-25% larger than their current mate or males that were similar size to their current mate. Female convict cichlids prefer larger males, therefore we predicted that the frequency of divorce would be hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Allowing females visual access to their current mate in competition with an alternate male who is larger leads to high levels of mate switching although independently, neither male size differences nor observing competition between size-matched individuals led to pair-bond instability (van Breukelen and Draud 2005). Our results support previous research, as although females had visual access to any male-male competition occurring in our experiments, all males were sized matched.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Allowing females visual access to their current mate in competition with an alternate male who is larger leads to high levels of mate switching although independently, neither male size differences nor observing competition between size-matched individuals led to pair-bond instability (van Breukelen and Draud 2005). Our results support previous research, as although females had visual access to any male-male competition occurring in our experiments, all males were sized matched.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, pair stability can breakdown if offspring are removed, and pairs re-form when offspring are returned (Lamprecht and Rebhan 1997). In the prespawning stage of the reproductive cycle, however, pair stability breaks down when females choose a new mate (van Breukelen and Draud 2005). The treatments differed in the number of available breeding sites given to groups of fish and were zero, one, or two.…”
Section: Discussionmentioning
confidence: 99%
“…Logically, when females do not choose dominant males, their preferences should be for traits unrelated to male dominance (e.g., Peterson et al 1999;Stapley 2008; also see Forsgren 1997). In convict cichlids, van Breukelen and Draud (2005) observed that females are more likely to ''divorce'' (i.e., switch mates after establishing a pair bond) after seeing their mate physically interact with a larger male. However, male size in the absence of this brief interaction did not influence divorce rate, suggesting that size as a cue alone is not enough for a female to judge competitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason for this unexpected result is that restraining the female caused the paired male to see the female as being no longer available for pair formation while the single male saw her as a potential mate. Previous studies have shown that females are continuously assessing their mate until spawning (Santangelo and Itzkowitz 2004;van Breukelen and Draud 2005) making the dissolution of the bond possible whenever a new male appears (Triefenbach and Itzkowitz 1998).…”
Section: Discussionmentioning
confidence: 99%